DIFFERENCES LEARNING OUTCOMES AT THE FOREHAND GROUNDSTROKES BEGINNER ATHLETES - Pujianto, Dian (UNIVERSITAS NEGERI MAKASSAR, 2021)
The purpose of this study was to determine the differences in the results of learning the skills of groundstrokes forehand tennis in novice athletes by using two different forms of learning media, namely demonstration media and video media. This research is an experimental research which was conducted in the city of Bengkulu in the province of Bengkulu in 2016. The population of this study was the 5th semester students who were new to tennis court, amounting to 20 students. The research sample used a total sample, the sample was divided into two groups, the first group used demonstration media and the second group used video media. Data were collected through tests and measurements of the skills of tennis groundstrokes. The results of data analysis with the t test with the SPSS 21 program show a coefficient of 0.048, this price is smaller than the coefficient of 0.05, so from this comparison it can be concluded that there is a difference in learning outcomes of tennis forehand grounstroke skills using demonstration media with media. video.